Risk of major cardiovascular events among incident dialysis patients: A Korean national population-based study. (1st November 2015) - Kim, Hyunwook; Kim, Kyoung Hoon; Ahn, Song Vogue; Kang, Shin-Wook; Yoo, Tae-Hyun; Ahn, Hyeong Sik; Hann, Hoo Jae; Lee, Shina; Ryu, Jung-Hwa; Yu, Mina; Kim, Seung-Jung; Kang, Duk-Hee; et al.
Abstract: Background: Dialysis patients are at high risk for cardiovascular diseases, but until now there have been no detailed analyses of the incidences among Asian patients initiating dialysis. The aims of this study were to determine the incidence rates of major adverse cardiac and cerebrovascular events (MACCE) and to compare them between incident HD patients and PD patients. Methods: We included all patients who had started dialysis between January 1, 2005 and December 31, 2008 in Korea, and analyzed 30, 279 eligible patients [22, 892 hemodialysis (HD) patients and 7387 peritoneal dialysis (PD) patients] by intention-to-treat. Median follow-up was 21.5 months. Results: The crude incidence rates were as follows: MACCE, 182 per 1000 patient-years (PY); major adverse cardiac events (MACE), 138/1000 PY; all-cause mortality, 116/1000 PY; non-fatal acute myocardial infarction (AMI), 18/1000 PY; target vessel revascularization (TVR), 17/1000 PY; and non-fatal stroke, 60/1000 PY. When comparing all baseline covariate-adjusted relative risks between HD and PD patients, HD is overall superior to PD in terms of MACCE. Further examined by each endpoint, all-cause mortality, non-fatal AMI, and TVR occurred significantly more frequently in patients on PD than in those on HD, whereas non-fatal hemorrhagic stroke occurred significantly more frequently in patients on HD than in those on PD. Conclusions: The incidence of MACCE may be different from Western dialysis patients. HD is overall superior to PD in terms of MACCE as an initial dialysis modality. Underlying mechanisms differentially affecting cardiovascular outcomes by dialysis modality remain to be further elucidated.